Analisa Kerawanan Banjir Kabupaten Bandung Dengan Software ARGIS - Amar Ardiansyah; Fahreza Irghi Budi. S; Zebina Hiya Reksa Fadillah; Isfak Ibnu Ahmad; Dika Ayu Safitri (Asosiasi Riset Ilmu Teknik Indonesia, 2024)
Flooding is one of the disasters that often occurs in Indonesia, there are several cities that are always subscribed to flooding, one of which is Bandung Regency. On this occasion the author analyzed the vulnerability map in Bandung Regency using ArcGIS software by processing annual rainfall data, land use parameters, slope data, land elevation, and soil texture with this data the author obtained a percentage value of the level of flood vulnerability in Bandung Regency. Areas that have low elevations tend to experience flooding every year. From the processed data, there are 8 sub-districts in Bandung Regency with a flood prone percentage of more than 50%, namely Ketapang, Margahayu, Dayeuh Kolot, Pameungpeuk, Bojong Soang, Margaasih, Rancaekek, and Baleendah sub-districts. Based on the analysis of the flood prone map, most of Bandung Regency has a flood prone level classified as 'Less Prone', with an area of 64,277.228 hectares.